Stress induced martensite at the crack tip in NiTi alloys during fatigue loading (Fracture and Structural Integrity, 2014)
Crack tip stress-induced phase transformation mechanisms in nickel-titanium alloys (NiTi) were analyzed by Digital Image Correlation (DIC), under fatigue loads. In particular, Single Edge Crack (SEC) specimens, obtained from a commercial pseudoelastic NiTi sheet, and an ad-hoc experimental setup were used, for direct measurements of the near crack tip displacement field by the DIC technique. Furthermore, a fitting procedure was developed to calculate the mode I Stress Intensity Factor (SIF), starting from the measured displacement field. Finally, cyclic tensile tests were performed at different operating temperature, in the range 298-338 K, and the evolution of the SIF was studied, which revealed a marked temperature dependence.
Keywords: Digital Image Correlation